Sistem Pendukung Keputusan Penerimaan Tenaga Unit Medis di RS Ari Canti dengan Metode Topsis - Wiwik Sri Rahayu Ginantra, Ni Luh; Yanti, Christina Purnama; Toraja, Dewa Gede (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Ari Canti Hospital selectively conducts selection in the company environment that is by selecting one by one application then do some test on applicants with several criteria. With a large number of applicants making the selection process takes a lot of time and effort, as well as applicant data and the outcomes of the applicants are not well archived. Based on the above problems, need a solution to problem-solving by making a Decision Support System to determine the appropriate applicants to become new employees by facilitating the selection of employees by predetermined criteria. The TOPSIS method is chosen because this method is a form of decision support method based on the concept that the best alternative not only has the shortest distance from the ideal solution but also has the longest distance Of the ideal solution. The result of the design of this Decision Support System is the system has been able to generate reports from the applicant rank calculation by the values that have been obtained on the criteria that have been determined. The calculation results of the Decision Support System is already by the calculations performed manually.